2002
DOI: 10.1002/ldr.484
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary landscape evolution: a framework for understanding contemporary erosion, southeast Spain

Abstract: Recent research into the long-term landscape development of a tectonically active terrain in arid SE Spain has revealed the significance of river capture in understanding current landscape instabilities (badlands and landslides). The river capture was initiated at c.100 ka BP and effected a 90 m base-level change at the point of capture. This stimulated a wave of incision to propagate through the landscape to 20 km upstream of the capture site. The net effect of the associated increase in erosion has been to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 49 publications
1
39
0
3
Order By: Relevance
“…Decadal scale erosion rates have also been calculated from digital elevation models (Ciccacci et al, 2008) and longer term incision rates have been calculated in relation to dated surfaces in Spain (Mather et al, 2002;Díaz-Hernández and Juliá, 2006), Israel and Canada (Bryan et al, 1987). Although badlands have been used to epitomize extreme or accelerated erosion, the limited number of published values for erosion rates varies by 3-4 orders of magnitude [e.g.…”
Section: Badland Erosion Ratesmentioning
confidence: 99%
“…Decadal scale erosion rates have also been calculated from digital elevation models (Ciccacci et al, 2008) and longer term incision rates have been calculated in relation to dated surfaces in Spain (Mather et al, 2002;Díaz-Hernández and Juliá, 2006), Israel and Canada (Bryan et al, 1987). Although badlands have been used to epitomize extreme or accelerated erosion, the limited number of published values for erosion rates varies by 3-4 orders of magnitude [e.g.…”
Section: Badland Erosion Ratesmentioning
confidence: 99%
“…However, the highest incision depths are associated with the catchments in the transition zone between the thin and thick till blanket areas. The valley cross-sections are used to compute the volume of material removed as described in Mather et al (2002) for each basin. The elevations associated with the drainage divides were used to construct a paleosurface of the NMB following a similar method to that described by Brocklehurst and Whipple (2002) and Montgomery and Lopez-Blanco (2003).…”
Section: Modern Day Processes: Watersheds and Erosionmentioning
confidence: 99%
“…Bryan, Campbell and Yair (1986) suggested that in the Dinosaur Provinical Park in Alberta, badland evolution has followed broad phases of incision and filling relating to relatively wetter and drier phases through the Holocene (see also Evans, Campbell and Lemmen, 2004, and similar arguments for the evolution of southern French badlands in Descroix and Gautier, 2002), although Evans (2000) has demonstrated that this landscape is also strongly controlled by inherited features from past glacial and periglacial processes. Initial formation of the South Dakota badlands seems to have been triggered by gullying as a response to base-level change (Mather, Stokes and Griffiths, 2002;Howard, 2009), and base-level change has also been implicated in Spanish gully systems (Griffiths et al, 2005), so that large-scale climate variability can also be seen to be important. However, gully formation and evolution is a complex process that may or may not indicate climatic control (Cooke and Reeves, 1976).…”
Section: Rcmentioning
confidence: 99%
“…This approach thus ties into the discussion above about tectonic and climatic impacts on badlands, but also other elements of landscape interconnectivity such as river capture (e.g. Mather, Stokes and Griffiths, 2002;Griffiths et al, 2005).…”
Section: Processes and Rates Of Badland Evolutionmentioning
confidence: 99%